2013
DOI: 10.1007/s10535-013-0357-6
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast ultrastructure of Hypericum perforatum plants regenerated in vitro after cryopreservation

Abstract: The ultrastructure of leaf mesophyll cells of in vitro cultured Hypericum perforatum L. plants regenerated after cryopreservation was studied. Electron microscopy analysis revealed that the chloroplasts in plants pretreated with abscisic acid and regenerated after cryopreservation were round, with increased amount of starch, rather small volume of the thylakoid system, and destroyed envelope. Plants pretreated with 0.3 M mannitol and cooled at rates of 0.1 or 0.3 °C min -1 possessed chloroplasts with high star… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The positive influence of the prolonged dehydration interval related to the lower rates of cooling was also confirmed for mesophyll cells of H. perforatum plants regenerated after cryopreservation ( Stoyanova-Koleva et al, 2013 ). TEM analyses revealed the increasing protective effect of mannitol at lower cooling velocities.…”
Section: Crucial Processes For Successful Cryopreservation In mentioning
confidence: 68%
See 3 more Smart Citations
“…The positive influence of the prolonged dehydration interval related to the lower rates of cooling was also confirmed for mesophyll cells of H. perforatum plants regenerated after cryopreservation ( Stoyanova-Koleva et al, 2013 ). TEM analyses revealed the increasing protective effect of mannitol at lower cooling velocities.…”
Section: Crucial Processes For Successful Cryopreservation In mentioning
confidence: 68%
“…Another way in which the cryoprotectant agents relate to restoration of the viability after cryostorage is preservation of the photosynthetic apparatus. The protective roles of ABA and mannitol were confirmed on cellular and sub-cellular levels by transmission electron microscopy (TEM) in H. perforatum and H. rumeliacum plants ( Stoyanova-Koleva et al, 2013 , 2015 ). The effect of ABA depended on the species, duration of the treatment and cooling regime; in H. perforatum , although no deleterious post-cryogenic alterations of the internal membrane system under 10-day pre-treatment with ABA followed by slow-cooling were seen, the destruction of the chloroplast membranes was observed after vitrification ( Stoyanova-Koleva et al, 2015 ).…”
Section: Crucial Processes For Successful Cryopreservation In mentioning
confidence: 95%
See 2 more Smart Citations
“…Later studies of in vitro regenerated plants after cryopreservation found that in the most critical photosynthetic organs, the leaves, there are deviations in the mesophyll structure and chloroplast ultrastructure, and these alterations are species-specific, which confirms the need to continue the research. These works revealed that examinations at the histological, cellular, and subcellular levels were necessary for evaluating plant regeneration capacity in vitro and during ex vitro acclimatization [Stoyanova- Koleva et al 2013Koleva et al , 2015. Nevertheless, many open questions that refer to the structural and functional status of the plants regenerated from recovered after cryo-treatment meristem remain and deserve further analysis.…”
Section: Introductionmentioning
confidence: 99%